Application of Immersive Technologies in Dealing with Suicidality (in Terms of Virtual Reality Technologies) - Shevchuk, Olha; Krupelnytska, Liudmyla (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Introduction. Suicidality stands as a significant public health concern. Each year suicides not only claim lives but also affect the surrounding environment of the individual, leading to various outcomes that require timely and appropriate actions. Factors such as inherent human rights, the economic aftermath of suicide, cultural and religious practices, and personal values could all serve as catalysts for enacting policies and practices for both preventing and addressing suicides. These very factors, in their unique combinations, could also serve as influences that either elevate the risk of or shield against the development of suicidal tendencies. The primary objective of this article is to analyze the empirical use of immersive technologies in addressing suicidality. Methods. The research methodology employed includes rigorous scientific methods such as the analysis of relevant scholarly literature, systematization, synthesis, and generalization. Results. Instances, where key social figures and stakeholders collaborated, demonstrated the most effective approach in preventing suicides. These collaborations not only enhance an individual’s overall well-being but also precisely addressed their specific situation, accounting for their distinct characteristics (comorbid conditions and symptoms, etc.). An example of a successful blend of interdisciplinary research and practical interventions in the context of suicidality is the integration of immersive technologies. These technologies, particularly virtual reality, provide a range of possibilities, such as: 1) creating controlled environments for cultivating coping skills and emotional regulation abilities; 2) enhancing the engagement and involvement of clients/patients in addressing their concerns; 3) enabling specialists to better cater to individual client needs through versatile settings. Discussion. However, comprehensive research and analysis are still required to consider the nuances of implementing these technologies. Factors like equipment costs, logistical considerations, training for service providers, potential technical glitches, and their consequences need to be accounted for. Additionally, the ethical dimensions of such interventions, including security, data privacy, confidentiality, potential risks of exacerbating suicidal tendencies, and the quality of human interaction throughout the intervention process, warrant further discussion. Overall, immersive technologies are demonstrating a range of advantages over traditional intervention methods, making them a promising avenue for continued exploration and application in the field of suicide prevention.